1999
DOI: 10.1093/intimm/11.10.1701
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of CD4 expression in T cells by the transcriptional repressor ZEB

Abstract: ZEB, an E-box binding transcriptional repressor, is an important regulator of T cell and muscle development. Targeted disruption of ZEB in mice resulted in a strong reduction of thymocytes and the few T cells that reached the mature stage were predominantly CD4(+). CD4 expression during the various stages of T cell differentiation is controlled at the transcriptional level by a complex array of regulatory elements in the CD4 gene locus, consisting of at least three enhancers, one promoter and one silencer. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…Instead, in cMyb seems broadly expressed in the early ectoderm of HH3-4 embryos (Fig. 4I), confirming reported northern and western blots (Karafiat et al, 2005), and providing further support for the possible participation of cMyb in Pax7 regulation.cMyb and ETS1 are known to cooperate in many different contexts (Dudek et al, 1992;McCracken et al, 1994;Postigo et al, 1997;Ratajczak et al, 1998;Brabletz et al, 1999;Betancur et al, 2010a). As there are ETS1 sites present in P7eNPBEΔ2, we tested the possible cooperation between ETS1 and cMyb to regulate P7eNPBE.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Instead, in cMyb seems broadly expressed in the early ectoderm of HH3-4 embryos (Fig. 4I), confirming reported northern and western blots (Karafiat et al, 2005), and providing further support for the possible participation of cMyb in Pax7 regulation.cMyb and ETS1 are known to cooperate in many different contexts (Dudek et al, 1992;McCracken et al, 1994;Postigo et al, 1997;Ratajczak et al, 1998;Brabletz et al, 1999;Betancur et al, 2010a). As there are ETS1 sites present in P7eNPBEΔ2, we tested the possible cooperation between ETS1 and cMyb to regulate P7eNPBE.…”
supporting
confidence: 80%
“…cMyb and ETS1 are known to cooperate in many different contexts (Dudek et al, 1992;McCracken et al, 1994;Postigo et al, 1997;Ratajczak et al, 1998;Brabletz et al, 1999;Betancur et al, 2010a). As there are ETS1 sites present in P7eNPBEΔ2, we tested the possible cooperation between ETS1 and cMyb to regulate P7eNPBE.…”
Section: Research Articlementioning
confidence: 99%
“…However, these studies were done using a T cell clone (DH10) that has already committed to the CD4 ϩ Th lineage. ZEB is another transcription factor found to repress CD4 expression, but again only in SP thymocytes, postpositive selection (8). The 434-bp CD4 silencer (3, 4) contains a remarkable five consensus binding sites for runt family transcription factors, making any runt family transcription factors that are expressed in DP thymocytes strong candidates for the factor responsible for down-regulation of CD4 in maturing thymocytes.…”
Section: Cd8mentioning
confidence: 99%
“…11 For the T-lineage, ZEB1 regulates T-cell development. [12][13][14] Loss of ZEB1 in knockout mice accelerates the development of adult T-cell leukemia. 15 In this study, we found that H. pylori-positive gastric diffuse large B-cell lymphomas had less lymph node metastasis and a better response to chemotherapy.…”
mentioning
confidence: 99%